Is sustainable certification's ability to combat greenwashing trustworthy? - Nygaard, Arne (Frontiers in Sustainability, 2023)
Certifications are considered crucial tools for tackling climate change, upholding human rights, and promoting the green transition. However, this critical review article highlights certain negative effects that can arise because of certifications. While empirical research indicates that certifications can increase the value of green brands and consumers' willingness to pay for certified products and sustainable performance, our review also underscores the behavioral risk of free riding as an unintended consequence. In addition, disruptive green technological and market transitions also lead to structural inertia in the organization of certifications. As such, the review recommends implementing counteractive measures to prevent eco-opportunism like free riding and to combat the issue of greenwashing that can occur with certifications.